Development of Standard Operating Protocols for the Optimization of Cannabis-Based Formulations for Medical Purposes - Francesca Baratta; Marco Simiele; Marco Simiele; Irene Pignata; Lorenzo Ravetto Enri; Riccardo Torta; Anna De Luca; Massimo Collino; Antonio D'Avolio; Antonio D'Avolio; Paola Brusa (Frontiers Media S.A., 2019)
Under current legislation in Italy, Cannabis for medical purposes may be administered orally in the form of decoction or Cannabis oil extract. The scientific literature reports a number of preparation methods, mainly for oils, but no study is available that compares thoroughly, from a technological viewpoint, the Cannabis-based formulations currently administered to patients. With this in mind, this research work aimed to carry out specific formulation studies to design standard operating procedures for the preparation and optimization of Cannabis-based galenic formulations. Both decoctions and oils were prepared under different operating conditions to identify the most efficient process for the production of formulations with a high concentration of decarboxylated delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). Regarding Cannabis oil, a new procedure has been developed that allows significantly higher recovery rates for THC and CBD compared with those for water-based extraction methods (decoction) and those for oil-based methods currently in use. Moreover, based on the results, it is possible to affirm that the prescription of Cannabis-based decoctions should not be the recommended first-choice solution for therapy, considering the low concentration of THC and CBD and, consequently, the high volume of decoction that the patient would have to ingest.